Diplomasi Publik Arab Saudi Dalam Mencapai Visi 2030: Studi Kasus Pengembangan Liga Sepak Bola Profesional Saudi - Alfarizi, Surya Maldini; Triantama, Febry (Universitas Medan Area, 2024)
This research discusses Saudi Arabia's public diplomacy efforts through the development of its professional football league which aims to achieve the 2030 vision. As one of the most popular and historic sports in the world, football has become an important instrument in a country's foreign policy, this is because Football has a big influence in influencing the public and establishing international relations. This research began by collecting and carefully examining all aspects of the public diplomacy efforts carried out by the Saudi Arabian government in its aim of achieving Vision 2030, which it launched in 2016. Based on the concept of Public Diplomacy and the theory of National Interest, this research focuses on The Saudi Arabian government's initiative in carrying out its public diplomacy activities through the development of its professional football league. The research also further analyzes Saudi Arabia's national interests that underlie its public diplomacy efforts. In this case, economic interests and national image interests are significant motivations that drive Saudi Arabia's ambitions in its public diplomacy efforts through the massive development of its professional football league. All the public diplomacy efforts have been placed under the interests of Saudi Arabia to make its professional football league a hope in achieving its 2030 vision.